Constructing and contesting identities and community membership in online football forums - Philippides, Angelo (My University, 2015)
The internet has provided a new medium of communication that has resulted in distinct forms of social interaction and provided a new social space in which people from all over the world come together as a community to discuss football. Within this space they are socialised, cultures are transmitted, social structures are reproduced and identity is transmitted. Thus the aim of this study was to understand how followers of a particular football team invoke and contest membership into the categories of football supporter and community of supporters in an online forum. The method used was Membership Categorisation Analysis (MCA) within the Conversation Analysis (CA) approach. The sample was a critical case study and consisted of interactions from a single discussion thread of an online football supporter forum. The results revealed that the Opening Post (OP) formed a space in which potential respondent identities and status as community members could be made relevant however implicitly provided constraints regarding how members were expected to respond. Agreeing members produced a community consensus on how other members should respond however as more members with disagreeing responses expressed their opinion, a more moderate community consensus emerged in which disagreement and agreement between members was not a requisite for contestation of community membership. When there was contestation for community membership and identity, members used collective pronouns, account-giving, partial agreement, category-tied predicates, vernacular specific to a team and phrases like “in my opinion” and “to me”. The study concluded that within an online setting, football supporter identity and community membership are dynamic processes that constantly change, are context-dependent and are managed by the members in order to achieve certain aims.
A Research Report submitted in partial fulfilment of the requirements for the degree of Master of Psychology by Coursework and Research Report in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 16 February 2015.